Optimisation of individual cardiovascular risk assessment in a German coronary artery disease cohort using a commercial test for genetic polymorphisms: a pilot study - Krohn, Jona B.; Neubauer, Clemens; Fischer, Simon; Oberkanins, Christian; Katus, Hugo; Gleißner, Christian A. (Acta cardiologica, 2023)
Assessment of cardiovascular risk using established risk scores such as ESC SCORE2 or PROCAM insufficiently emphasise the role of genetic factors. We hypothesise that commercially available genetic assays may provide additional information on hereditary cardiovascular risk in a timely and cost-efficient manner. In a cohort of 51 patients treated for coronary artery disease (CAD) at University Hospital Heidelberg, Germany, a subgroup of patients with “unstable” CAD (i.e. recurrent acute coronary syndrome) was identified and compared to patients with “stable” disease (i.e. chronic coronary syndrome). Gene array analysis using a commercial assay for 15 potentially pathogenic polymorphisms revealed our cohort’s genetic risk profile regarding atherosclerotic/thromboembolic events. Improvement of cardiovascular risk assessment based on established risk scores was analysed using net reclassification, logistic regression and receiver operating characteristic (ROC) analysis. Discriminatory capacity of traditional risk scores such as SCORE2 or PROCAM with regard to stable and unstable CAD groups was poor (ROC AUC <0.5). Patients with “unstable” CAD exhibited a significantly increased frequency of pathogenic eNOS 894 T and MTHFR 1298 C polymorphisms compared to “stable” CAD patients, and information on these polymorphisms individually as well as combinations with additional polymorphisms included in the assay such as ACE D/D or PAI-1 5 G variants markedly improved risk prediction compared to SCORE2/PROCAM alone (ROC AUC ≥0.75). Commercially available assays for genetic polymorphisms may provide valuable information on individual genetic cardiovascular risk, potentially guiding future primary and/or secondary preventative therapies for coronary artery disease.